Public control and digital technologies in the context of constitutional and legal responsibility implementation among officials - Naser Abdulridha, Jaafar (2021)
The study is devoted to one of the topical areas of modern jurisprudence - digital technologies in law, public control and responsibility. The article discusses some problems of public control implementation and analyzes the main forms of this institution implementation in the activities of officials of state authorities.